Estimation Of The Vocal Folds Vibration Fundamental Frequency by Higer Order Spectrum - Wiesław WSZOŁEK; Maciej KŁACZYŃSKI (Archives of Acoustics)
Research studies carried out by many authors prove that a lot of information concerning the phonation activity of speech organ can be gathered by accurate determination of parameters related to the fundamental tone F0. It is also reckoned that the knowledge of acoustic parameters based on the measured time dependence of the source’s F0 parameter during the phonation process contains valuable information regarding larynx pathology, personal features as well as the physical and emotional condition of the speaker. At present many methods are applied for determination of the F0 function. The present work discusses the feasibility and accuracy of fundamental frequency determination based on Higher-Order Spectra Analysis (HOSA).